Canopy temperature of bean genotypes under two soil humidity conditions - Filho, José Moacir P. Lima (Pesquisa Agropecuaria Brasileira, 2014)
Canopy temperatures of Bat-66, Bat-70 and G-3776 bean (Phaseolus vulgaris L.) genotypes submitted to well-watered and water deficiency conditions were evaluated hourly between 7:00 A.M. and 5:00 PM, during three consecutive days, using the infrared thermometry technique, under glasshouse environment. It was observed that genotypes canopy temperatures were significantly higher under water deficiency than under well-watered conditions. Nevertheless, Bat-70 had a lower canopy temperature under water deficiency than Bat-66 and G-3776. The possibility of using canopy temperature to detect crop water stress and on primary screenning of drought tolerant bean genotypes was suggested.